Translation Strategies for Speech Features of Characters in Fictional Texts (a Case Study of Speech of Upper Class Representatives) - M. N. Kulikova (Дискурс)
Introduction. The paper analyses different means used for conveying the phonetic features of the speech of upper class representatives in English fiction, in particular in the works of Charles Dickens and John Galsworthy. The author focuses on functions of phonographic stylisation of the aristocratic speech and discusses the techniques and strategies for rendering this phenomenon into the Russian language.Methodology and sources. When selecting examples for analysis, we used the method of corpus analysis, which made it possible to establish the frequency of using a particular phonographic means, as well as the continuous sampling method used to analyse a specific technique of phonographic stylisation. Methods of linguistic, sociolinguistic and translation analysis were used to analyse specific examples of phonographic stylisation and their translations into the Russian language. The novels by Charles Dickens and John Galsworthy were used to carry out the research.Results and discussion. When translating the speech of upper class representatives into the Russian language, phonographic means can be rendered only in those cases when they perform a parody function. Otherwise, phonographic means are not conveyed but might be substituted or compensated by lexical and syntactical means, which can be considered a natural consequence because of the difference in the traditions of representing the speech of aristocrats in English and Russian literary traditions.Conclusion. Phonographic means and phonographic stylisation are the most important component of the artistic representation of character’s speech in general, and the speech of upper class representatives in particular. Consequently, this phenomenon is a multifaceted linguistic problem in the theory of translation. This study outlines the main directions of analysis of phonographic stylisation while rendering the speech of aristocrats, but this problem is far from being solved. Other cases of using phonographic stylisation may be the subject of further research into contrasting and translation aspects.